Study and simulation with VHDL-AMS of the electrical impedance of a piezoelectric ultrasonic transducer - Toufik Merdjana; Abdelhafid Chaabi (International Journal of Power Electronics and Drive Systems (IJPEDS), 2019)
Ultrasonic transducers are a key element that governs the performances of both generating and receiving ultrasound in an ultrasonic measurement system. Electrical impedance is a parameter sensitive to the environment of the transducer; it contains information about the transducer but also on the medium in which it is immersed. Several practical applications exploit this property. For this study, the model is implemented with the VHDL-AMS behavioral language. The simulations approaches presented in this work are based on the electrical Redwood model and its parameters are deduced from the transducer electroacoustic characteristics.